Real- time Financial reporting : Role promoting completeness and timeliness in Investment & profit distribution decision - عبد الله سلمان حسين; جاسم رؤى احمد (Journal of Economics and Administrative Sciences, 2017)
The accounting information that is produced by any System a user either entering or leaving, since the needs of the users began to evolve where he became the information provided by the current reporting system that does not meet their requirements in terms of users began to demand information, more quickly, and as a result of the needs of the user accounting system and the development of information and communications technology has emerged a new system (real- time reporting system), which has the ability to produce information at the moment of data gathered, it is no longer dependent on local circumstance, but this case has become a global response where the computer has become a cornerstone of the culture of the communities in the various spheres of life, the tool of knowledge tools, including the current era is the era of information, systems and search for the best uses of the lowest cost and time, but this has increased the importance of information in the modern era as a result of technological development, which has coincided with the development of computers, which led to the availability of time and effort and the speed of data and information transfer to its users.